2020
DOI: 10.3390/ijms21041528
|View full text |Cite
|
Sign up to set email alerts
|

PbMYB120 Negatively Regulates Anthocyanin Accumulation in Pear

Abstract: Subgroup 4 R2R3 MYBs play vital roles in the regulation of anthocyanin biosynthesis. However, there is limited knowledge regarding the functions of MYB repressors in pear (Pyrus × bretschneideri). Here, PbMYB120 was identified as a potential regulator of anthocyanin biosynthesis. A phylogenetic analysis revealed that PbMYB120 was clustered into the FaMYB1-like clade of the subgroup 4 R2R3 MYBs. PbMYB120 was expressed higher in red peels than in green peels in five pear cultivars. PbMYB120 expression was positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…It is responsible for encoding regulatory factors and controlling the transcription and activity of multiple enzymes in biosynthesis pathways. MYB [88][89][90], bhLh [91] and WDR [92] are several major transcription factors that adjust anthocyanin synthesis. MYB or MYB-bhLh-WDR complexes (MBW) are combined onto the promoter of structural genes to regulate downstream genes [1].…”
Section: Regulatory Genesmentioning
confidence: 99%
“…It is responsible for encoding regulatory factors and controlling the transcription and activity of multiple enzymes in biosynthesis pathways. MYB [88][89][90], bhLh [91] and WDR [92] are several major transcription factors that adjust anthocyanin synthesis. MYB or MYB-bhLh-WDR complexes (MBW) are combined onto the promoter of structural genes to regulate downstream genes [1].…”
Section: Regulatory Genesmentioning
confidence: 99%
“…It must be pointed out that without any partners, MrMYB6 displayed no suppression on the promoters of either MrANS or MrUFGT in anthocyanin-specific pathway (Figure 3C). On the contrary, researches have revealed that several R2R3-MYB repressors such as VcMYBC2, PbMYB120, MaMYB4, and FaMYB1 on their own were sufficient to inhibit anthocyanin accumulation in many fruits such as blueberry, pear, banana, and strawberry (Aharoni et al, 2001;Song et al, 2020;Deng et al, 2021;Li et al, 2021). Therefore, we supposed that there might be other MYB TFs independently down-regulating anthocyanin accumulation in bayberries, which deserved further studies.…”
Section: Discussionmentioning
confidence: 90%
“…In Arabidopsis, AtMYB32 and AtMYB4 knockout mutant enhanced the yield of lignin and sinapate esters by increasing the expression level of the C4H gene. In addition, MYB4 acts as a repressor of phenylpropanoid metabolisms by downregulating the expression of genes encoding arogenate Dehydratase 6, which cat-alyzes the final step in phenylalanine biosynthesis [132,145]. MdMYB6 isolated from apple, reduced the anthocyanin accumulation upon its overexpression in Arabidopsis thaliana.…”
Section: Myb Transcription Factors Act As Repressors Through C2/erf/tllfr Motifmentioning
confidence: 99%